Endovascular therapy in acute basilar artery occlusion: A retrospective single‐centre Australian analysis. Issue 1 (8th November 2018) - Shore, Timothy H; Harrington, Timothy J; Faulder, Kenneth; Steinfort, Brendan
Abstract: Introduction: Stroke caused by basilar artery occlusion (BAO) is a rare but potentially devastating neurological condition, with poor outcomes and high mortality rates, approaching 70–90%. Success of intravenous and intra‐arterial thrombolysis in BAO is variable, leading to Endovascular Therapy (EVT) being utilized to a greater degree in this clinical setting. We investigate the use of EVT in BAO with regard to success of revascularization and patient mortality/outcome. Methods: Retrospective patient data was collected from medical records and radiology information systems. Results: Twenty‐eight patients underwent EVT for BAO between 2010–17, with successful revascularization in 21/28 (75%) and an inpatient mortality rate of 39%. Successful revascularization correlated with lower mortality ( P = 0.0001). Better revascularization and mortality rates occurred between 2013–17 ( P = 0.007, 0.04). An average time to EVT of 16.8 hours was observed between 2010–17 but this did not correlate significantly with increased mortality. Basilar stenting correlated with lower revascularization, higher mortality and basilar artery reocclusion post EVT ( P = 0.021, 0.022, 0.022). EVT times over 2 and 2.5 hours respectively associated with lower revascularization rates and higher mortality ( P = 0.04, 0.022). Higher mortality was seen with intra‐procedural complications and symptomatic intracranial haemorrhage, non‐posterior circulation infarction and basilar artery reocclusion post EVT ( P = 0.016, 0.03, 0.016, 0.016). Basilar atheroma correlated with intra‐procedural complications and EVT times over 2 hours ( P = 0.038, 0.004). Conclusion: Within the limitations of an underpowered study, we observed a benefit of EVT in acute BAO. With future multicentre trials, EVT will likely become the standard of care in acute BAO.